2021
DOI: 10.1371/journal.pone.0250956
|View full text |Cite
|
Sign up to set email alerts
|

Covichem: A biochemical severity risk score of COVID-19 upon hospital admission

Abstract: Clinical and laboratory predictors of COVID-19 severity are now well described and combined to propose mortality or severity scores. However, they all necessitate saturable equipment such as scanners, or procedures difficult to implement such as blood gas measures. To provide an easy and fast COVID-19 severity risk score upon hospital admission, and keeping in mind the above limits, we sought for a scoring system needing limited invasive data such as a simple blood test and co-morbidity assessment by anamnesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
11
0
3
Order By: Relevance
“…Many studies have reported early markers of COVID-19 severity that are capable of predicting clinical evolution towards severe complications, such as demographic predictors, laboratory parameters, chest radiographic abnormalities, and other clinical characteristics such as comorbidities or oxygen dependency [9]. Several studies have integrated clinical and paraclinical variables or signs and symptoms, among others, into a clinical prognostic score for the clinical management of COVID-19 patients, to better establish the prognosis of the disease [10,11]. The utility of multivariable machine learning predictive models has also been explored to stratify the patients at admission into predefined groups of disease severity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported early markers of COVID-19 severity that are capable of predicting clinical evolution towards severe complications, such as demographic predictors, laboratory parameters, chest radiographic abnormalities, and other clinical characteristics such as comorbidities or oxygen dependency [9]. Several studies have integrated clinical and paraclinical variables or signs and symptoms, among others, into a clinical prognostic score for the clinical management of COVID-19 patients, to better establish the prognosis of the disease [10,11]. The utility of multivariable machine learning predictive models has also been explored to stratify the patients at admission into predefined groups of disease severity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is calculated using a regression function that includes two comorbidities (obesity (defined as a BMI ≥30) and cardiovascular disease (CVD; coronary artery diseases such as angina and myocardial infarction, heart failure, cardiomyopathy, abnormal heart rhythms, valvular heart disease, aortic aneurysms, heart transplant, peripheral artery disease, thromboembolic disease, venous thrombosis and stroke)) and five laboratory test results (Na, albumin, ferritin, LDH, and CK; Supplement 1). It was derived and externally validated by Bats et al, who used the 0.5 (50%) value of this estimate as a threshold to assign patients to positive and negative Covichem groups [ 4 ]. We collected all data and then calculated the estimate and Covichem groups using the regression function described in Bats et al…”
Section: Methodsmentioning
confidence: 99%
“…Bats et al developed a score, called the Covichem score, for predicting a patient's risk of severe illness with COVID-19. This score can be calculated at hospital admission [ 4 ]. It uses clinical parameters and commonly available laboratory results and does not require imaging results or advanced testing.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bats et al. designed a framework of clinical characteristics consisting of 26 variables to learn a probability distribution for severe and risk-free patients [20] . Selection of the best predictors was made using the Akaike information criterion and the classifier was learnt as logistic regression.…”
Section: Related Workmentioning
confidence: 99%